The Agreement of Complex Sentence and its Meanings in the Last Quarter of Holy Quran- Selected Models (Raparin Journal of Humanities (RJH), 2021)
This study is entitled (The Structural Agreement of Complex Sentence and its Meanings in the Last Quarter of Holy Quran - Selected Models)  the Noble Qur’an through the varying linguistic methods that are relied upon in the formulation of sentences and texts, and among these methods: (constructive) which does not bear truth and lies in and of itself.Given the importance of this topic, the study came as an application to the last quarter of the Holy Qur’an; To reveal the manifestations of the rhetorical inimitability in it, as well as to find the connotations contained in the construction methods in different rhetorical contexts, and these methods are characterized by their various suggestive and semantic ability that vary in the diversity of the tools and contexts of the method.The research includes a study of the imperative construction represented in the style of (the command, the prohibition, the question, the wish, and the call), a theoretical and applied study at the same time.